Multi-element gas sensor based on surface plasmon resonance: recognition of alcohols by using calixarene films - Kostyukevych, K.V.; Khristosenko, R.V.; Shirshov, Yu.M.; Kostyukevych, S.A.; Samoylov, A.V.; Kalchenko, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
This work is devoted to development of a multi-element gas sensor based on surface plasmon resonance (SPR) to recognize some alcohols. As sensitive layers capable to change their optical properties when interacting with volatile alcohol molecules, we investigated bulk-porous sorbents – calixarenes (tret-butyl-calix[4,6,8]arenes (С[4]А, С[6]А, С[8]А), tetra-amyl-calix[4] resorchinolaren (C[4]Re). Each calixarene was studied to obtain its kinetic concentration SPR characteristics for interaction with ethanol, isopropanol and penthanol vapors. To realize SPR measurements, the sensitive calixarene films (d ∼ 100 nm) were deposited on a gold film (d ∼ 45 nm) by using the method of thermal evaporation in vacuum. Experimental multi-element SPR device was designed as based on the analysis of TV image obtained for the studied array of calixarene films and tested using saturated ethanol vapors.